A Role for the Claustrum in Salience Processing? - Smith, Jared B.; Watson, Glenn D. R.; Liang, Zhifeng; Liu, Yikang; Zhang, Nanyin; Alloway, Kevin D. (Frontiers in Neuroanatomy, 2019)
The claustrum (CLA) is a subcortical structure, present only in mammals, whose function remains uncertain. Previously, using resting-state functional magnetic resonance imaging (rs-fMRI) in awake head-fixed rats, we found evidence that the CLA is part of the rodent homolog of the default mode network (DMN; Smith et al., 2017). This network emerged as strong functional connections between the medial prefrontal cortex (mPFC), mediodorsal (MD) thalamus, and CLA in the awake state, which was not present following administration of isoflurane anesthesia. In the present report, we review evidence indicating that the rodent CLA also has connections with structures identified in the rodent homolog of the salience network (SN), a circuit that directs attention towards the most relevant stimuli among a multitude of sensory inputs (Seeley et al., 2007; Menon and Uddin, 2010). In humans, this circuit consists of functional connections between the anterior cingulate cortex (ACC) and a region that encompasses both the CLA and insular cortex. We further go on to review the similarities and differences between the functional and anatomical connections of the CLA and insula in rodents using both rs-fMRI and neuroanatomical tracing, respectively. We analyze in detail the connectivity of the CLA with the cingulate cortex, which is a major node in the SN and has been shown to modulate attention. When considered with other recent behavior and physiology studies, the data reveal a role for the CLA in salience-guided orienting. More specifically, we hypothesize that limbic information from mPFC, MD thalamus, and the basolateral amygdala (BLA) are integrated by the CLA to guide modality-related regions of motor and sensory cortex in directing attention towards relevant (i.e., salient) sensory events.